PENERAPAN METODE MAUT PADA PEMILIHAN BIMBINGAN INTENSIF TERBAIK DI PEMATANGSIANTAR - Situmorang, Yolanda Agustina; Dalimunthe, Nurhafidah; Parlina, Iin; Lubis, Muhammad Ridwan (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2018)
Education is a sector that greatly determines the quality of a nation. The failure of education has implications for the failure of a nation, the success of education also automatically brings the success of a nation. In the world of education, it should pay attention to the elements of education, which include: students, educators, software, management, facilities and infrastructure and stake holders. Assets needed in education are human resources that are quality. Quality resources can be from students, the community, as well as from educators. In education, there is a level of education which starts from kindergarten, elementary school, junior high school, high school and university. Higher education is the education unit of higher education providers. Higher education students are called students, while college educators are called lecturers. According to the type, universities are divided into two, namely; state universities and private universities. Among students who want to go to college, many of the students want to go to state universities. So that many students and parents make their children for intensive guidance so that they can be accepted at the desired state universities. Intensive guidance is a learning aid activity for students or students that aims to make students achieve optimal learning achievement.Keywords: Education, Higher Education, Intensive Guidance